Determination of paracetamol in pharmaceutical samples by spectrophotometric method - Pasha, Chand (Eclética Química, 2020)
It is described the use of 1,3 dinitrobenzene or 2,4 dinitrophenyl hydrazine is used as coupling agent for the spectrophotometric determination of paracetamol. This method is easy and simple based on the reaction of acid hydrolysis of paracetamol to produce p-aminophenol, which in turn reacts with nitrite in acidic standard to form diazonium ion, which is coupled with coupling agent in basic standard to produce azo dyes. The formed dyes follow Beer’s law in the range of 0.8-20.5 mg mL-1 of paracetamol with 1, 3 dinitrobenzene or 0.5-18.4 mg mL-1 of paracetamol with 2,4 dinitrophenyl hydrazine with absorption maxima at 429 nm or 430 nm. The molar absorptivity and Sandell’s sensitivity of paracetamol with 1,3 dinitrobenzene or paracetamol with 2,4 dinitrophenyl hydrazine azo dyes were 1.965×104 L mol-1 cm-1 or 2.776×104 L mol-1 cm-1, and 7.692×10-3 mg cm-2 or 5.698×10-3 mg cm-3 respectively. The dyes formed are stable for more than 12 h. The optimal reaction circumstances and other analytical parameters are evaluated. Interference due to foreign organic compounds have been studied. The method has been effectively applied to the determination of paracetamol in pharmaceutical samples.